NILAI-NILAI PENDIDIKAN ISLAM DALAM TAYANGAN YOUTUBE CHANNEL POLISI MOTRET - Anisa Nikma Aidina; Mifta Khurohmah Tri Wahyuni (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The quantity and quality of a person, including indicators of the value of Islamic education, is a significant development and becomes the basis for mental development in order to provide educational output in accordance with the expectations of the wider community. This is what shapes the personality of each individual with moral, ethical, and cultural values. On social media, researchers see creativity on YouTube channels with an entertaining genre. Therefore, the authors found the Polisi Motret channel with library research methods with entertaining genres but that do not abandon Islamic educational values. The main objective of the Polisi Motret channel research which is based on the value of Islamic education is to form the personality of the community so that it has ethical values that are in line with the principles of benefit and virtue in the form of the life principle of every Muslim who is faithful, pious, and has noble character in everyday life.Keywords:Â Value of Islam Education; YouTube Channel; Polisi Motret